Site effects in Mexico City basin: Past and present. Issue 121 (June 2019) - Mayoral, J.M.; Asimaki, D.; Tepalcapa, S.; Wood, C.; Roman-de la Sancha, A.; Hutchinson, T.; Franke, K.; Montalva, G.
Abstract: Due to the unique subsoil conditions prevailing in the Mexico City basin, seismic risk has been strongly correlated to site effects. Thus, during the Mw 8.1 09/19/1985﻿ subduction fault earthquake, and its strong aftershock Mw 7.5 09/21/1985, extensive damage was observed in the area, along with the loss of thousands of lives, despite these events had an epicentral distance of around 430 km from Mexico City. The observed damage was mostly due to site affects originated by the high plastiCity clay deposits found in the basin, which lead to large amplifications, and duration elongation of the ground motions coming from the epicenter. In addition, a frequency content modification occurs, which in turn, leads to a double resonance effect between the incoming ground motions, soil deposits, and the damaged buildings. Exactly 32 years after this devastating event, the Mw 7.1 09/19/2017 normal fault earthquake, reminded us of the importance of accounting for site effects, and most importantly the need to carry out a proper characterization of basin geometry, soil profile configuration, hydraulic conditions, and maintenance-structure periodic assessments of the building stock in Mexico City. This is required to reduce uncertainties of seismic vulnerability studies for extreme-event seismic hazard scenarios. In this paper, the role of site response and seismic soil-structure interaction as key factors responsible of the observed damage in the City is revisited, through series of 3D finite difference models of typical structure-foundation-soil typologies found at the areas where most of the damage was observed, highlighting its clear impact in the final damage distribution observed around the City. Graphical abstract: Site effects and observed damagefx1 Highlights: Seismic risk in Mexico City is been strongly correlated to site effects. One dimensional analyses successfully predicted recorded ground motions at benchmark SCT site. Seismic response of common soil-building typologies were studied using three-dimensional models. Larger seismic demand occurred for structural and soil periods of around 1 s. Initial ground and building conditions coupled with seismic demand led to the observed damage.